Maternal foetal attachment and perceived stress during pregnancy - Srivastava, Akankshi; Bhatnagar, Pallavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In recent years, the construct of maternal foetal attachment (MFA) has gained a lot of attention. The significance of the bond between the mother and her child she is carrying has led researchers to study how the expecting woman’s feelings towards the unborn child, have long lasting effects on the child. Although several psychological factors, such as maternal anxiety, attitude towards the baby and access to foetal imaging procedures, have been established to significantly influence a mother’s attachment to her foetus, there seems to be a paucity of empirical work on the relationship between maternal stress during pregnancy and maternal foetal attachment. The present research is a step in this direction and purports to explore this relationship. Methods: The study explored the relationship between MFA and stress using the maternal foetal attachment scale by Cranley and the stress scale of the ADSS by Bhatnagar et al. The sample consisted of 53 pregnant women with a mean age of 26.4. Results: The results suggest a significant negative relationship between stress and MFA, r=-0.55 (p<0.01). Stress also showed a negative correlation with the subscales of MFAS, with highly stressed women reporting lower levels of self-giving behavior, fewer thoughts of role taking and lesser interactive behavior with the foetus. Conclusions: High stress during pregnancy could impede the formation of a strong bond between the expecting woman and her foetus. Thus the best practices during pregnancy should aim to reduce stress and encourage maternal foetal interaction.